2018
DOI: 10.1097/pas.0000000000001002
|View full text |Cite
|
Sign up to set email alerts
|

Novel EWSR1-SMAD3 Gene Fusions in a Group of Acral Fibroblastic Spindle Cell Neoplasms

Abstract: Benign/low-grade fibroblastic tumors encompass a broad spectrum of tumors with different morphologies and molecular genetic abnormalities. However, despite significant progress in recent genomic characterization, there are still tumors in this histologic spectrum that are difficult to classify, lacking known molecular characteristics. Triggered by a challenging congenital spindle cell neoplasm arising in the heel of a 1-year-old boy, we applied RNA sequencing for genetic discovery and identified a novel EWSR1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 22 publications
3
56
0
Order By: Relevance
“…The identification of disease‐defining molecular alterations is gradually enabling more refined subclassification of these tumors, and this can be exploited for diagnostic purposes. This is exemplified by reports of NTRK ‐rearranged fibroblastic tumors, EWSR1‐SMAD3 ‐rearanged fibroblastic tumor, and PRDM10 ‐rearranged soft tissue tumor…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The identification of disease‐defining molecular alterations is gradually enabling more refined subclassification of these tumors, and this can be exploited for diagnostic purposes. This is exemplified by reports of NTRK ‐rearranged fibroblastic tumors, EWSR1‐SMAD3 ‐rearanged fibroblastic tumor, and PRDM10 ‐rearranged soft tissue tumor…”
Section: Introductionmentioning
confidence: 77%
“…purposes. This is exemplified by reports of NTRK-rearranged fibroblastic tumors, [2][3][4] EWSR1-SMAD3-rearanged fibroblastic tumor, 5,6 and PRDM10rearranged soft tissue tumor. 7 Our groups recently independently encountered a distinctive soft tissue neoplasm characterized by fusions involving PRRX1 and NCOA1.…”
mentioning
confidence: 80%
“…An EWSR1–SMAD3 fusion was recently identified as the genetic hallmark of a novel benign fibroblastic neoplasm with predilection for acral soft tissues . The index case occurred in the foot of an infant male, presenting as an ill‐defined dermal and subcutaneous nodule with an infiltrative border.…”
Section: New Genetic Advances In Fibroblastic Pediatric Lesionsmentioning
confidence: 71%
“…Unsupervised clustering of the whole transcriptome data showed that the EWSR1–SMAD3 fusion positive tumor clustered together with other fibroblastic tumors, including a CAF with FN1–EGF fusion, a LPF lacking genetic abnormalities, and a LPF‐NT with TPR–NTRK1 fusion. Interestingly, ERG mRNA was strongly upregulated, finding further supported by diffuse nuclear immunoexpression of ERG protein …”
Section: New Genetic Advances In Fibroblastic Pediatric Lesionsmentioning
confidence: 99%
See 1 more Smart Citation